An electric airplane: Assessing the effect of travelers' perceived risk, attitude, and new product knowledge. (July 2019) - Han, Heesup; Yu, Jongsik; Kim, Wansoo
Abstract: The electric transition of the airline industry is emerging, closely following the automobile industry. Nonetheless, very little is known about airline customers' readiness for traveling on the electric alternative of an airplane. This study was designed to examine customers' intricate decision-making process for adopting electric airplanes and paying conventional flight prices for such electric-airplane flights. Our results from the structural analysis revealed that reducing customers' perceived risk and increasing new product knowledge is critical in boosting trust and positive attitude toward electric airplanes that significantly elicit their adoption and pay intentions. In addition, the effectiveness of the higher-order structure of perceived risk was uncovered, and both attitude and trust were significant mediators. Our theoretical framework satisfactorily accounted for behavioral intentions. Our results help airline practitioners invent efficient strategies to boost customers' willingness to travel on electric airplanes adapting the electric transition of the airline industry. Highlights: We investigated customer readiness for traveling on electric airplanes. Factors that boost customer willingness to pay for electric airplanes were identified. Reducing perceived risk was the key for the electric transition of the airline industry. The impact of trust was identified. We have presented a direction to expand the understanding of customer attitude/behavior towards the electric aircraft.